ADVANCED PRACTICES IN ENVIRONMENTAL EDUCATION AND EDUCATION - Lochinbek Abdirasulov (American Journals, 2025)
The article examines environmental education and analyzes a number of foreign experiences. A number of opinions were expressed regarding the introduction of environmental education from developed countries into our country.
Keywords: Environmental education, foreign experience, environment, nature, environmental thinking.